Putting Things in Perspective: The COVID-19 Pandemic Period, Distance Education and Beyond - AYYİLDİZ, Pinar; YILMAZ, Adem (Anemon Mus Alparslan Universitesi Sosyal Bilimler Dergisi, 2021)
This research aims to approach distance education activities and to COVID-19 from a different perspective during the pandemic process. It is seen that many studies in the literature were prepared with a single data collection tool or a limited number of data. In this context, it was thought to bring a different perspective by making data diversification. This research has the ethics committee document issued number 1, dated 25.03.2021, with decision number 96 obtained from the Ethical Board of Kastamonu University. In the research process, one of the basic mixed-method designs, combining (diversification) pattern was used. 865 teachers candidates from 9 different departments and 4 different grade levels, studying in the education faculty of a state university in Turkey in the 2020-2021 academic year, participated in the research. In the research, metaphor application, a word association test, a semi-structured interview and a 20-question scale prepared by the researchers were used as data collection tools. The obtained data were analyzed using descriptive, content and inferential statistical methods. As a result of the research, 7 different categories and a total of 153 different metaphors were found out. As a result of the word association test, 6 main concepts and a total of 46 sub-concepts formed. The semi-structured interview and scale results demonstrate that the attitudes of the teacher candidates towards the technical infrastructure, measurement-evaluation, and distance education process are low and that their satisfaction rates are below their expectations.
Keywords: Uzaktan Eğitim; COVID-19; Mixed-Method; Öğretmen Adayları; Distance Education; Karma Yöntem; Teacher Candidates; 4. Education; 16. Peace & justice; 3. Good health; 13. Climate action; 10. No inequality